Safety and immunogenicity of the novel H4:IC31 tuberculosis vaccine candidate in BCG-vaccinated adults: Two phase I dose escalation trials - Norrby, Maria; Vesikari, Timo; Lindqvist, Lars; Maeurer, Markus; Ahmed, Raija; Mahdavifar, Shahnaz; Bennett, Sean; McClain, J. Bruce; Shepherd, Barbara M.; Li, Daner; Hokey, David A.; Kromann, Ingrid; et al. (Vaccine, 2017)
•H4:IC31 vaccination was well tolerated with an acceptable safety profile.•H4:IC31 vaccination elicited persistent antigen-specific CD4+ T cell responses.•H4:IC31 triggered T cell expansion, IFNγ production and multifunctional Th1 cells.•Optimal antigen-adjuvant doses were 5, 15, or 50 μg of H4 plus 500 nmol of IC31. Novel vaccine strategies are required to provide protective immunity in tuberculosis (TB) and prevent development of active disease. We investigated the safety and immunogenicity of a novel TB vaccine candidate, H4:IC31 (AERAS-404) that is composed of a fusion protein of M. tuberculosis antigens Ag85B and TB10.4 combined with an IC31® adjuvant. BCG-vaccinated healthy subjects were immunized with various antigen (5, 15, 50, 150μg) and adjuvant (0, 100, 500nmol) doses of the H4:IC31 vaccine (n=106) or placebo (n=18) in two randomized, double-blind, placebo-controlled phase I studies conducted in a low TB endemic setting in Sweden and Finland. The subjects were followed for adverse events and CD4+ T cell responses. H4:IC31 vaccination was well tolerated with a safety profile consisting of mostly mild to moderate self-limited injection site pain, myalgia, arthralgia, fever and post-vaccination inflammatory reaction at the screening tuberculin skin test injection site. The H4:IC31 vaccine elicited antigen-specific CD4+ T cell proliferation and cytokine production that persisted 18weeks after the last vaccination. CD4+ T cell expansion, IFN-γ production and multifunctional CD4+ Th1 responses were most prominent after two doses of H4:IC31 containing 5, 15, or 50μg of H4 in combination with the 500nmol IC31 adjuvant dose. The novel TB vaccine candidate, H4:IC31, demonstrated an acceptable safety profile and was immunogenic, capable of triggering multifunctional CD4+ T cell responses in previously BCG-vaccinated healthy individuals. These dose-escalation trials provided evidence that the optimal antigen-adjuvant dose combinations are 5, 15, or 50μg of H4 and 500nmol of IC31. Trial registration: ClinicalTrials.gov, NCT02066428 and NCT02074956.